Integrated all-solid-state secondary battery
By coating the mixed slurry of conductive ceramic material and polymer on the electrode and absorbing the liquid electrolyte into the composite film, the existing all-solid secondary battery manufacturing process and large interface resistance are solved, and the effect of simplifying the manufacturing process and improving the battery characteristics is achieved.
Patent Information
- Application Number
- CN202510021426.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-09-28
- Filing Date
- 2018-09-27
- Publication Date
- 2025-04-11
AI Technical Summary
The manufacturing process of existing all-solid secondary batteries is complicated, resulting in an increase in the interface resistance between the electrode and the solid phase electrolyte, affecting the characteristics of the battery.
By coating a mixed slurry including a conductive ceramic material, a polymer and a solvent onto the electrode, and after the solvent is dried, the liquid electrolyte is absorbed into the formed composite film, the manufacturing process of the battery is simplified and the interface resistance is reduced.
The manufacturing process of all-solid secondary batteries is simplified, production costs are reduced, and the characteristics of the battery's interface resistance are improved.
Smart Images

Figure CN119812457A_ABST
Abstract
Description
[0001] This application is a divisional application based on the Chinese patent application with application number 201880063454.X (international application number PCT / KR2018 / 011347), application date September 27, 2018, and invention name “Integrated all-solid secondary battery”. Technical Field
[0002] The present invention relates to an integrated all-solid-state secondary battery (Integrated all-solid-state secondary battery) in which electrodes and solid electrolytes are integrated, and a method for manufacturing the same, wherein the integrated all-solid-state secondary battery is manufactured by coating a mixed slurry including a conductive ceramic material, a polymer and a solvent onto an electrode, and then absorbing a liquid electrolyte after the solvent is dried. Background Art
[0003] In the prior art, the units required for a secondary battery, such as electrodes, electrolytes, and separators, are manufactured separately and then laminated together to manufacture a secondary battery. All-solid secondary batteries are also made in the same way as the prior art, in that a solid-phase electrolyte is manufactured through an independent process and then laminated with electrodes. Since the prior art method is to laminate the electrodes and solid-phase electrolytes after manufacturing them separately, there is a problem of increased interface resistance between the electrodes and the solid-phase electrolytes. Therefore, additional units (for example, a buffer layer including a polymer and a conductive ceramic material) and processes are required to reduce the interface resistance between the electrodes and the solid-phase electrolytes. In addition, the prior art solid-phase electrolytes have low ionic conductivity at room temperature and high interface resistance with the electrodes, so there is a problem of low battery characteristics. Summary of the invention
[0004] Problems to be solved by the invention
[0005] The purpose of the present invention is to simplify the manufacturing process of all-solid secondary batteries by solving the problems in the manufacturing process of existing all-solid secondary batteries. According to the present invention, not only can the manufacturing cost of all-solid secondary batteries be reduced, but also the characteristics of all-solid secondary batteries can be improved.
[0006] The object of the present invention is to provide a new solid electrolyte that solves the problems of existing solid-phase electrolytes.
[0007] Solutions for solving problems
[0008] Existing secondary batteries are made by laminating the various units (electrodes, electrolytes, and separators, etc.) used to assemble the battery after they are manufactured separately. All-solid secondary batteries are also made in the same way as existing processes. They are made by making solid-phase electrolytes by an independent process and then laminating them with electrode layers. This process is not only complicated, but the solid-phase electrolyte is exposed to moisture in the air for a long time. In addition, since the electrodes and solid-phase electrolytes are manufactured separately and then mechanically laminated, the interface resistance will increase. Therefore, an additional process is required to reduce the interface resistance.
[0009] The present invention applies a mixed slurry including a conductive ceramic material, a polymer and a solvent to an electrode, and then evaporates the solvent, thereby simplifying the manufacturing process of the all-solid-state battery. In addition, the side reactions in the secondary battery can be reduced by reducing the time that the constituent materials that act as electrolytes are exposed to moisture in the air. The present invention manufactures a solid-phase electrolyte by absorbing a liquid electrolyte into a composite film including a ceramic material and a polymer after the solvent has evaporated. Therefore, according to the present invention, the interface resistance between the electrode and the electrolyte can be effectively reduced without the need for an additional process (for example, forming a buffer layer).
[0010] Effects of the Invention
[0011] According to the present invention, the cost can be reduced by simplifying the manufacturing process of the all-solid secondary battery. In addition, the present invention can improve the interface resistance and other characteristics of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a schematic diagram of the manufacturing process of an integrated all-solid-state secondary battery.
[0013] Figure 2 It is a schematic diagram of an integrated all-solid secondary battery made by coating a mixed slurry including a conductive ceramic material, a polymer and a solvent onto the positive electrode, removing the solvent by drying, and absorbing the liquid electrolyte into a composite film including a conductive ceramic material and a polymer (formed by removing the solvent), and then covering the negative electrode.
[0014] Figure 3 This is a schematic diagram of an integrated all-solid secondary battery according to another embodiment, in which a first mixed slurry including a conductive ceramic material, a polymer and a solvent is applied to a positive electrode, the solvent is removed by drying, and then a second mixed slurry including a conductive ceramic material, a polymer and a solvent (different from the first mixed slurry) is applied to a first composite film including a conductive ceramic material and a polymer formed by removing the solvent, and the solvent is removed by drying to form a multilayer composite film in which the second composite film is laminated on the first composite film, and a liquid electrolyte is absorbed into the multilayer composite film, which is then covered with a negative electrode.
[0015] Figure 4This is a schematic diagram of an integrated all-solid secondary battery according to another embodiment, in which a first mixed slurry including a conductive ceramic material, a polymer and a solvent is applied to a positive electrode, the solvent is removed by drying, and a liquid electrolyte is absorbed into a first composite film including a conductive ceramic material and a polymer to form a positive electrode unit integrating the positive electrode and the first solid electrolyte. At the same time or in sequence, a second mixed slurry including a conductive ceramic material, a polymer and a solvent (different from the first mixed slurry) is applied to a negative electrode, the solvent is removed by drying, and a liquid electrolyte is absorbed into a second composite film including a conductive ceramic material and a polymer to form a negative electrode unit integrating the negative electrode and the second solid electrolyte. Thereafter, the positive electrode unit and the negative electrode unit are bonded together.
[0016] Figure 5 is in accordance with Figure 2 The charge and discharge curves of the integrated all-solid-state secondary battery made by the method.
[0017] Figure 6 is in accordance with Figure 3 The charge and discharge curves of the integrated all-solid-state secondary battery made by the method.
[0018] Figure 7 is in accordance with Figure 4 The charge and discharge curves of the integrated all-solid-state secondary battery made by the method.
[0019] Figure 8 It is in accordance with Figure 2 An integrated all-solid secondary battery made by a method and a battery made according to an existing method (using Figure 2 A graph showing the measurement and comparison of the cell resistance of all-solid-state secondary batteries made of the same material. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are as follows.
[0021] 1. A method for manufacturing an integrated all-solid secondary battery, which comprises applying a mixed slurry comprising a conductive ceramic material, a polymer and a solvent to either side of an electrode, removing the solvent by drying, and allowing a liquid electrolyte to absorb into a composite film comprising a conductive ceramic material and a polymer formed by removing the solvent, and covering the opposite electrode.
[0022] 2. A method for manufacturing an integrated all-solid secondary battery, which comprises applying a first mixed slurry comprising a conductive ceramic material, a polymer and a solvent to either side of an electrode, removing the solvent by drying, and then applying a second mixed slurry comprising a conductive ceramic material, a polymer and a solvent to a first composite film comprising a conductive ceramic material and a polymer formed by removing the solvent, removing the solvent by drying, thereby forming a multilayer composite film in which the second composite film is laminated on the first composite film, and allowing a liquid electrolyte to be absorbed into the multilayer composite film, and then covering the opposite electrode, wherein the second mixed slurry is different from the first mixed slurry.
[0023] 3. A method for manufacturing an integrated all-solid secondary battery, comprising applying a first mixed slurry comprising a conductive ceramic material, a polymer and a solvent to a positive electrode, removing the solvent by drying, and allowing a liquid electrolyte to absorb a first composite film comprising a conductive ceramic material and a polymer formed by removing the solvent, to form a positive electrode unit in which the positive electrode and the first solid electrolyte are integrated.
[0024] A second mixed slurry including a conductive ceramic material, a polymer and a solvent is applied to the negative electrode, the solvent is removed by drying, and a liquid electrolyte is absorbed into a second composite film including a conductive ceramic material and a polymer formed by removing the solvent, to form a negative electrode unit in which the negative electrode and the second solid electrolyte are integrated, and then the positive electrode unit and the negative electrode unit are laminated,
[0025] The second mixed slurry is different from the first mixed slurry, and the processes of forming the positive electrode unit and the negative electrode unit are performed simultaneously or sequentially.
[0026] 4. According to the method for manufacturing an integrated all-solid secondary battery described in Embodiment 2, the multilayer composite film further includes a composite film different from the first composite film and the second composite film.
[0027] 5. According to the method for manufacturing an integrated all-solid secondary battery described in Embodiment 3, any one or both of the positive electrode unit and the negative electrode unit further includes a composite film different from the first composite film and the second composite film.
[0028] 6. According to the method for manufacturing an integrated all-solid secondary battery according to any one of embodiments 1 to 5, when the sum of the conductive ceramic material and the polymer is taken as 100 weight %, the amount of the conductive ceramic material in the mixed slurry is 40 weight % to 99 weight %.
[0029] 7. According to the method for manufacturing an integrated all-solid secondary battery according to any one of embodiments 1 to 5, when the sum of the conductive ceramic material and the polymer is taken as 100 weight %, the amount of the polymer in the mixed slurry is 1 weight % to 60 weight %.
[0030] 8. According to the method for manufacturing an integrated all-solid secondary battery according to any one of embodiments 1 to 7, when the composite membrane including the conductive ceramic material and the polymer is taken as 100 parts by weight, the amount of liquid electrolyte absorbed into the composite membrane is 1 to 40 parts by weight.
[0031] 9. According to the method for manufacturing an integrated all-solid secondary battery described in any one of embodiments 1 to 8, the solvent used in the mixed slurry of the above-mentioned conductive ceramic material, polymer and solvent is N-methyl-2-pyrrolidone (NMP) or its derivatives, acetone or its derivatives, ethanol or its derivatives, methanol or its derivatives, dimethylacetamide (DMAc) or its derivatives, tetrahydrofuran (THF) or its derivatives, dimethylformamide (DMF) or its derivatives, distilled water or a mixture thereof.
[0032] 10. According to the method for manufacturing an integrated all-solid secondary battery according to any one of embodiments 1 to 9, the liquid electrolyte is a lithium salt or a sodium salt dissolved in a non-aqueous organic solvent or an ionic liquid solvent or a mixture thereof.
[0033] 11. According to the method for manufacturing an integrated all-solid secondary battery described in embodiment 10, the non-aqueous organic solvent is a carbonate, ester, ether, ketone, alcohol, aprotic solvent or a combination thereof.
[0034] 12. According to the method for manufacturing an integrated all-solid secondary battery described in embodiment 10, the above-mentioned ionic liquid solvent is imidazolium, pyridinium, pyrrolidinium, sulfonium, pyrazolium, ammonium, morpholinium, phosphonium, piperidinium or a combination thereof.
[0035] 13. According to the method for manufacturing an integrated all-solid-state secondary battery described in embodiment 10, the above-mentioned lithium salt is LiClO4, LiPF6, CF3SO2NLiSO2CF3 (LiTFSI), Li[N(SO2F)2](LiFSI), Li[B(C2O4)2](LiBOB), LiAsF6, (fluorosulfonyl)(trifluoromethanesulfonyl)lithium imide (LiFTFSI) or a combination thereof.
[0036] 14. According to the method for manufacturing an integrated all-solid secondary battery described in embodiment 10, the above-mentioned sodium salt is NaClO4, NaPF4, NaPF6, NaAsF6, NaTFSI, Na[(C2F5)3PF3](NaFAP), Na[B(C2O4)2](NaBOB), Na[N(SO2F)2](NaFSI), NaBeti(NaN[SO2C2F5]2) or a combination thereof.
[0037] 15. According to the method for manufacturing an integrated all-solid-state secondary battery described in any one of embodiments 1 to 5, the conductive ceramic material is lithium oxide, lithium sulfide, lithium phosphate, amorphous ionic conductivity material, sodium superion conductor (NASICON), sodium sulfide or sodium oxide.
[0038] 16. According to the method for manufacturing an integrated all-solid secondary battery described in embodiment 15, the lithium oxide conductive ceramic material is Li-Al2O3, Li-β-Al2O3, Li-TiO2, Li-BaTiO3, Li-SiO2, (La, Li)TiO3 (LLTO) ((La, Li) = La or Li), Li5La3Ta2O 12 、Li6La2CaTa2O 12 、Li4SiO4Li3BO 2.5 N 0.5 、Li9SiAlO8、Li6La2ANb2O 12 (A=Ca or Sr), Li2Nd3TeSbO 12 、Li7La3Zr2O 12 (LLZO), Li5La3Ta2O 12 , Al2O3 or Li9SiAlO8.
[0039] 17. According to the method for manufacturing an integrated all-solid secondary battery described in embodiment 15, the lithium sulfide conductive ceramic material is Li 10 GeP2S 12 、Li7P2S 11 , Li 3.25 Ge 0.25 P 0.75 S4(LGPS), Li2S-Si2S5, Li2S-Ga2S3-GeS2, Li2S-Sb2S3-GeS2, Li2S-P2S5, Li2S-P2S5-Li4SiO4 or Li 3.25 -Ge 0.25 -P 0.75 S4 (Thio-LISICON).
[0040] 18. According to the method for manufacturing an integrated all-solid-state secondary battery described in Embodiment 15, the above-mentioned lithium phosphate-based conductive ceramic material is Li 1+x Al x Ge 2-x (PO4)3 (0 < x < 2) (LAGP), Li 1+x Ti 2-x Al x (PO4)3 (LTAP) (0 < x < 2), Li 1+x Ti 2-x Al x Si y (PO4) 3-y (0 < x < 2, 0 < y < 3), LiAl x Zr 2-x (PO4)3 (0 < x < 2) or LiTi x Zr 2-x (PO4)3 (0 < x < 2).
[0041] 19. According to the method for manufacturing an integrated all-solid-state secondary battery described in Embodiment 15, the above-mentioned amorphous ion conductive material is: phosphorous-based glass, oxide-based glass, or oxide-sulfide based glass.
[0042] 20. According to the method for manufacturing an integrated all-solid-state secondary battery described in Embodiment 15, the above-mentioned sodium oxide-based conductive ceramic material is Na3Zr2Si2PO 12 .
[0043] 21. According to the method for manufacturing an integrated all-solid secondary battery described in any one of embodiments 1 to 20, the above-mentioned polymer is polyvinylidene fluoride (PVdF) or its copolymer, poly(vinylidene fluoride-co-trifluoroethylene) or its copolymer, polyethylene glycol (PEO) or its copolymer, polyacrylonitrile (PAN) or its copolymer, poly(methyl methacrylate) (PMMA) or its copolymer, polyvinyl chloride or its copolymer, polyvinyl pyrrolidone (PVP) or its copolymer, polyimide (PI) or its copolymer, polyethylene (PE) or its copolymer, polyurethane (PU) or its copolymer, polypropylene (PP) or its copolymer, poly(propylene oxide) (PP0 ) or its copolymers, poly(ethyleneimine) (PEI) or its copolymers, poly(ethyl sulfide) (PES) or its copolymers, poly(vinyl acetate) (PVAc) or its copolymers, poly(ethylene succinate) (PESc) or its copolymers, polyesters or their copolymers, polyamines or their copolymers, polysulfides or their copolymers, siloxane-based or its copolymers, styrene butadiene rubber (SBR) or its copolymers, carboxymethyl cellulose (CMC) or its copolymers, or their derivatives, or their combinations.
[0044] 22. A method for manufacturing an integrated all-solid secondary battery, which is packaged by pressing and packaging the integrated all-solid secondary battery described in any one of embodiments 1 to 21.
[0045] 23. An integrated all-solid secondary battery manufactured according to any one of the methods of embodiments 1 to 22.
[0046] 24. An integrated all-solid secondary battery, which is encapsulated by pressing and encapsulating the integrated all-solid secondary battery manufactured by any one of the methods in embodiments 1 to 23.
[0047] 25. According to the integrated all-solid secondary battery described in embodiment 23, the thickness of the solid electrolyte between the positive electrode and the negative electrode is 20 μm to 150 μm.
[0048] 26. According to the integrated all-solid secondary battery described in embodiment 24, the thickness of the solid electrolyte between the positive electrode and the negative electrode is 20 μm to 150 μm.
[0049] Hereinafter, the present invention will be described in more detail.
[0050] When the sum of the above-mentioned conductive ceramic material and the polymer is calculated as 100 weight %, the conductive ceramic material may be 40 weight % to 99 weight %, and the polymer may be 1 weight % to 60 weight %. The conductive ceramic material may preferably be 60 weight % to 99 weight %, more preferably 70 weight % to 99 weight %, further preferably 80 weight % to 99 weight %, and most preferably 90 weight % to 99 weight %. The conductive ceramic material is more preferably 60 weight % to 90 weight %, and further preferably 70 weight % to 80 weight %. The polymer may be 1 weight % to 40 weight %, or 1 weight % to 30 weight %, or 1 weight % to 20 weight %, or 1 weight % to 10 weight %. The polymer is preferably 10 weight % to 40 weight %, and more preferably 20 weight % to 30 weight %.
[0051] When the composite membrane including the conductive ceramic material and the polymer is calculated as 100 parts by weight, the above-mentioned liquid electrolyte can be 1 to 40 parts by weight, preferably 10 to 40 parts by weight, more preferably 10 to 30 parts by weight, and further preferably 10 to 20 parts by weight.
[0052] The solvent used in the above-mentioned mixed slurry including conductive ceramic material, polymer and solvent can be N-methyl-2-pyrrolidone (NMP) or its derivatives, acetone or its derivatives, ethanol or its derivatives, methanol or its derivatives, dimethylacetamide (DMAc) or its derivatives, tetrahydrofuran (THF) or its derivatives, dimethylformamide (DMF) or its derivatives, distilled water or a mixture thereof.
[0053] The conductive ceramic material may be a lithium oxide containing oxygen in the crystal structure, for example, Li-Al2O3, Li-β-Al2O3, Li-TiO2, Li-BaTiO3, Li-SiO2, (La, Li)TiO3 (LLTO) ((La, Li) = La or Li), Li5La3Ta2O 12 、Li6La2CaTa2O 12 、Li4SiO4Li3BO 2.5 N 0.5 、Li9SiAlO8、Li6La2ANb2O 12 (A=Ca or Sr), Li2Nd3TeSbO 12 、Li7La3Zr2O 12 (LLZO), Li5La3Ta2O 12 , Al2O3, Li9SiAlO8; lithium sulfides including sulfur in their crystal structure, e.g., Li 10 GeP2S 12 、Li7P2S 11 , Li3.25 Ge 0.25 P 0.75 S4 (LGPS), Li2S - Si2S5, Li2S - Ga2S3 - GeS2, Li2S - Sb2S3 - GeS2, Li2S - P2S5, Li2S - P2S5 - Li4SiO4, Li 3.25 -Ge 0.25 -P 0.75 S4 (Thio - LISICON); lithium phosphate - based materials including phosphorus in the crystal structure, e.g., Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (0 < x < 2, preferably 0 < x < 1), Li 1+x Ti 2-X Al X (PO4)3 (LTAP) (0 < x < 2, preferably 0 < x < 1), Li 1+x Ti 2-x Al x Si y (PO4) 3-y (0 < x < 2, 0 < y < 3, preferably 0 < x < 1, 0 < y < 1), LiAl x Zr 2-x (PO4)3 (0 < x < 2, preferably 0 < x < 1), LiTi x Zr 2-x (PO4)3 (0 < x < 2, preferably 0 < x < 1); amorphous ion - conductive materials, e.g., phosphorous - based glass, oxide - based glass, oxide - sulfide based glass; NASICON; sodium sulfide - based materials; or sodium oxide - based materials, e.g., Na3Zr2Si2PO 12 。
[0054] The polymer may be: polyvinylidene fluoride (PVdF) or its copolymer, poly(vinylidene fluoride-co-trifluoroethylene) or its copolymer, polyethylene glycol (PEO) or its copolymer, polyacrylonitrile (PAN) or its copolymer, poly(methyl methacrylate) (PMMA) or its copolymer, polyvinyl chloride or its copolymer, polyvinyl pyrrolidone (PVP) or its copolymer, polyimide (PI) or its copolymer, polyethylene (PE) or its copolymer, polyurethane (PU) or its copolymer, polypropylene (PP) or its copolymer, poly(propylene oxide) (PPO) or its copolymer, poly(ethyleneimine) (PEI) or its copolymer, poly(ethyl sulfide) (PES) or its copolymer, poly(vinyl acetate) (PVAc) or its copolymer, poly(ethylene succinate) (PESc) or its copolymer, polyester or its copolymer, polyamine or its copolymer, polysulfide or its copolymer, siloxane-based or its copolymer, styrene butadiene rubber (SBR) or its copolymer, carboxymethyl cellulose (CMC) or its copolymer or its derivatives. The above polymers may also be mixtures of the above substances.
[0055] The above-mentioned liquid electrolyte can be formed by dissolving lithium salt or sodium salt in a non-aqueous organic solvent or an ionic liquid solvent or a mixture thereof, but is not limited thereto, and can include all types of liquid electrolytes commonly used in the technical field. The above-mentioned non-aqueous organic solvent can be a carbonate, an ester, an ether, a ketone, an alcohol, an aprotic solvent or a combination thereof. The above-mentioned ionic liquid solvent can be a solvent of an imidazolium, pyridinium, pyrrolidinium, sulfonium, pyrazolium, ammonium, morpholinium, phosphonium, piperidinium cation or a combination thereof. The structure of the ionic liquid cation is as follows:
[0056]
[0057] The lithium salts for the above liquid electrolyte can be LiClO4, LiPF6, CF3SO2NLiSO2CF3 (LiTFSI), Li[N(SO2F)2] (LiFSI), Li[B(C2O4)2] (LiBOB), LiAsF6, lithium fluorosulfonyl-trifluoromethanesulfonylimide (LiFTFSI), or a combination thereof.
[0058] The sodium salts for the above liquid electrolyte can be NaClO4, NaPF4, NaPF6, NaAsF6, NaTFSI, Na[(C2F5)3PF3] (NaFAP), Na[B(C2O4)2] (NaBOB), Na[N(SO2F)2] (NaFSI), NaN[SO2C2F5]2 (NaBeti), or a combination thereof.
[0059] When the above all-solid-state secondary battery includes a multilayer composite film, the composite film formed on the positive electrode uses a composite film having excellent electrical stability and characteristics relative to the positive electrode, and the composite film formed on the negative electrode uses a composite film having excellent electrical stability and characteristics relative to the negative electrode.
[0060] The composite film formed on the positive electrode preferably uses a ceramic material with excellent ionic conductivity. Lithium oxides, lithium phosphates, lithium sulfides, etc. can be used. The better the ionic conductivity of the ceramic material used, the better the electrochemical characteristics. For example, the composite film formed on the positive electrode preferably uses a ceramic material with a conductivity greater than 10 -3 S / cm, such as Li 1+x Ti 2-X Al X (PO4)3 (LTAP) (0 < x < 2), Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (0 < x < 2), Li 3x La 2 / 3-x TiO3 (LLTO) (0 < x < 2 / 3). In addition, as the ceramic material of the composite film formed on the positive electrode, Li2S-P2S5, Li2O-SiO2, Li7La3Zr2O 12 (LLZO), Li-β-Al2O3, Li 3.25 Ge 0.25 P 0.75 S4 (LGPS) can also be used.
[0061] The composite film formed on the negative electrode can use A12O3, garnet (such as Li6La2BaTa2O12 、Li7La3Zr2O 12 (LLZO)), composites (Composite) (for example, LiX-Al2O3 (X can be 1 and N)) and other ceramic materials. The ceramic material used to form the composite film at the negative electrode depends on the type of negative electrode used in the secondary battery. For example, when lithium is used as the negative electrode, it is preferred not to use ceramics containing Ti, Si, S, and Ge. When graphite (carbon), silicon, and germanium are used as the negative electrode, it is preferred not to use ceramics containing Ti and S. In addition, as the ceramic material of the composite film formed at the negative electrode, β-Al2O3, Li2O-SiO2, Li 3.25 Ge 0.25 P 0.75 S4(LGPS),Li 1+X Al x Ge 2-x (PO4)3(LAGP)(0 <x<2)。
[0062] The polymer used in the composite film formed on the positive electrode can be polyvinylidene fluoride (PVdF) or its copolymer, poly(vinylidene fluoride-co-trifluoroethylene) or its copolymer, polyethylene glycol (PEO) or its copolymer, polyacrylonitrile (PAN) or its copolymer, poly(methyl methacrylate) (PMMA) or its copolymer, polyvinyl chloride or its copolymer, polyvinyl pyrrolidone (PVP) or its copolymer, polyimide (PI) or its copolymer, polyethylene (PE) or its copolymer, polyurethane (PU) or its copolymer, polypropylene (PP) or its copolymer, poly( The invention relates to poly(propylene oxide) (PPO) or its copolymer, poly(ethyleneimine) (PEI) or its copolymer, poly(ethyl sulfide) (PES) or its copolymer, poly(vinyl acetate) (PVAc) or its copolymer, poly(ethylene succinate) (PESc) or its copolymer, polyester or its copolymer, polyamine or its copolymer, polysulfide or its copolymer, siloxane-based or its copolymer, styrene butadiene rubber (SBR) or its copolymer, carboxymethyl cellulose (CMC) or its copolymer, or their derivatives, or their combinations.
[0063] When the charging voltage is 4.4 V or more, polyvinylidene fluoride (PVdF) or a copolymer thereof is preferably used. In addition, as a polymer used for the composite film formed in the positive electrode, polyacrylonitrile (PAN) or a copolymer thereof is preferably used.
[0064] The polymers used for the composite film formed on the negative electrode can be the same as those used for the composite film formed on the positive electrode. Preferably, polyacrylonitrile (PAN)-based or its copolymers, polyurethane (PU)-based or its copolymers with excellent strength and electrochemical stability are used. In addition, styrene-butadiene rubber (SBR)-based or its copolymers, carboxymethyl cellulose (CMC)-based or its copolymers can also be used as the polymers for the composite film formed on the negative electrode.
[0065] For the composite film formed on the positive electrode, polyvinylidene fluoride (PVdF)-based or its copolymers are used as the polymer, and ceramic materials selected from lithium phosphate-based, lithium oxide-based, lithium sulfide-based and their mixtures are used as the ceramic materials; for the composite film formed on the negative electrode, polyvinylidene fluoride (PVdF)-based or its copolymers are used as the polymer, and lithium phosphate-based ceramic materials are used as the ceramic materials. Thus, a multilayer composite film can be fabricated.
[0066] For the composite film formed on the positive electrode, polyvinylidene fluoride (PVdF)-based are used as the polymer, and ceramic materials selected from Li 1+x Ti 2-X Al X (PO4)3 (LTAP) (0 < x < 2), Li7La3Zr2O 12 (LLZO), Li2S-P2S5 and their mixtures are used as the ceramic materials; for the composite film formed on the negative electrode, polyvinylidene fluoride (PVdF)-based are used as the polymer, and Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (0 < x < 2) are used. Thus, a multilayer composite film can be fabricated.
[0067] For the composite film formed on the positive electrode, polyvinylidene fluoride (PVdF)-based or its copolymers are used as the polymer, and ceramic materials selected from lithium phosphate-based, lithium oxide-based, lithium sulfide-based and their mixtures are used as the ceramic materials; for the composite film formed on the negative electrode, polyvinylidene fluoride (PVdF)-based or its copolymers are used as the polymer, and lithium oxide-based ceramic materials are used as the ceramic materials. Thus, a multilayer composite film can be fabricated.
[0068] For the composite film formed on the positive electrode, polyvinylidene fluoride (PVdF)-based, polyvinylidene fluoride-trifluoroethylene (PVdF-TrFE) or their mixtures are used as the polymer, and ceramic materials selected from Li 1+x Ti 2-X Al XCeramic materials of (PO4)3(LTAP) (0 < x < 2), (La,Li)TiO3 (LLTO), Li2S-P2S5 and their mixtures; for the composite film formed on the negative electrode, polyvinylidene fluoride (PVdF) - based, polyvinylidene fluoride - trifluoroethylene (PVdF - TrFE) or their mixtures are used as polymers, and ceramic materials selected from A12O3, β - Al2O3, Li7La3Zr2O 12 (LLZO) and their mixture ceramic materials. Thus, a multilayer composite film can be fabricated.
[0069] For the composite film formed on the positive electrode, polyacrylonitrile (PAN) - based or its copolymers are used as polymers, and ceramic materials selected from lithium phosphate - based, lithium oxide - based, lithium sulfide - based and their mixtures are used as ceramic materials; for the composite film formed on the negative electrode, polyacrylonitrile (PAN) - based or its copolymers are used as polymers, and lithium sulfide - based ceramic materials are used as ceramic materials. Thus, a multilayer composite film can be fabricated.
[0070] For the composite film formed on the positive electrode, polyacrylonitrile (PAN) - based is used as the polymer, and the ceramic material is selected from Li 1+x Ti 2-X Al X (PO4)3(LTAP) (0 < x < 2), Li7La3Zr2O 12 (LLZO), Li2S - P2S5 and their mixture ceramic materials; for the composite film formed on the negative electrode, polyacrylonitrile (PAN) - based is used as the polymer, and the ceramic material is selected from Li 3.25 Ge 0.25 P 0.75 S4(LGPS), Li2O - SiO2 and their mixture ceramic materials. Thus, a multilayer composite film can be fabricated.
[0071] In the above - mentioned all - solid electrolytes, lithium ions or sodium ions move through the following three paths. Among them, (1) is the main movement path.
[0072] (1) Movement through the contacted ceramic (pumping movement)
[0073] (2) Movement through the liquid electrolyte
[0074] (3) Movement across the ceramic material and the liquid electrolyte Specific embodiments
[0076] The embodiments of the present invention are described in detail below. The specific embodiments are only provided as examples of the present invention, and the present invention is not limited thereto. The scope of the present invention is only determined by the following claims.
[0077] The present invention applies a mixed slurry including a conductive ceramic material, a polymer, and a solvent to an electrode, evaporates the solvent, absorbs the liquid electrolyte, and then covers the counter electrode. Therefore, compared with the existing method, the present invention can more easily manufacture an integrated all-solid secondary battery.
[0078] Methods for absorbing the liquid electrolyte include dipping, dripping and pouring. ), etc., but not limited to these.
[0079] Methods for applying the mixed slurry to the electrode include printing, doctor blade coating, spin coating, spray coating, and the like.
[0080] The mixed slurry is made by mixing more than 75% by weight of a conductive ceramic material and less than 25% by weight of a polymer in a solvent, N-methyl-2-pyrrolidone (NMP). After the slurry is evenly applied to the electrode by printing, scraping, spin coating or spraying, the solvent is completely removed by drying. In addition, 20% by weight of a liquid electrolyte is absorbed into the composite film from which the solvent is removed. LiNi is used as the positive electrode. 0.6 Co 0.2 Mn 0.2 O2, and graphite is used as the negative electrode to produce an integrated all-solid secondary battery.
[0081] Figure 1 Schematic diagram of a manufacturing process of an integrated all-solid secondary battery according to an embodiment of the present invention.
[0082] Figure 2 This is a schematic diagram of the process of making an integrated all-solid secondary battery by covering the negative electrode after making a unit integrating the positive electrode and the all-solid electrolyte. 1.3 Al 0.3 Ge 1.7 The mixed slurry prepared by mixing (PO4)3(LAGP) and 25 wt% of the polymer polyvinylidene fluoride (PVdF) in N-methyl-2-pyrrolidone (NMP) solvent is applied to the positive electrode, and N-methyl-2-pyrrolidone (NMP) is evaporated by heat treatment, and 1MLiPF6 in the liquid electrolyte ethylene carbonate / dimethyl carbonate (EC / DMC, 1:1vol) is absorbed according to 20 wt% of the LAGP and PVdF composite film. Then the negative electrode is covered to complete the integrated all-solid secondary battery. The thickness of the composite film between the electrodes is 30μm.
[0083] Figure 3This is a schematic diagram of the process of making an integrated all-solid secondary battery by covering the negative electrode after manufacturing a unit integrating the positive electrode and the multi-layer all-solid electrolyte. 1.3 Al 0.3 Ti 1.7 A mixed slurry prepared by mixing (PO4)3(LATP) and 25 wt% of polymer polyvinylidene fluoride (PVdF) in N-methyl-2-pyrrolidone (NMP) solvent is applied to the positive electrode, and N-methyl-2-pyrrolidone (NMP) is evaporated by heat treatment, and a mixed slurry prepared by mixing 75 wt% of lithium conductive ceramic material Al2O3 and 25 wt% of polymer polyvinylidene fluoride (PVdF) in N-methyl-2-pyrrolidone (NMP) solvent is applied again thereon, and heat treatment is performed again to evaporate N-methyl-2-pyrrolidone (NMP), and 20 wt% of the multilayer composite film of the first composite film of LTAP and PVdF and the second composite film of Al2O3 and PVdF is absorbed in 1M LiPF6 of liquid electrolyte ethylene carbonate / dimethyl carbonate (EC / DMC, 1:1 vol). Then the negative electrode is covered to complete the integrated all-solid secondary battery. The polymer and solvent of the composite slurry phase used here can be the same or different, but for the conductive ceramic material, it is necessary to use a material suitable for the positive electrode in the positive electrode and a different material suitable for the negative electrode in the negative electrode. The total thickness of the two composite films between the electrodes is 80 μm.
[0084] Figure 4 This is a schematic diagram of the process of manufacturing a unit integrating the positive electrode and the all-solid electrolyte, and then bonding the two units together to make an integrated all-solid secondary battery. 1.3 Al 0.3 Ti 1.7A mixed slurry prepared by mixing (PO4)3(LATP) and 25 wt% of the polymer polyvinylidene fluoride (PVdF) in N-methyl-2-pyrrolidone (NMP) solvent is applied to the positive electrode, and the solvent is completely evaporated by drying. A mixed slurry prepared by mixing 75 wt% of the lithium conductive ceramic material Al2O3 and 25 wt% of the polymer polyvinylidene fluoride (PVdF) in N-methyl-2-pyrrolidone (NMP) solvent is applied to the negative electrode, and the solvent is completely evaporated by drying. In addition, 1M LiPF6 in the liquid electrolyte ethylene carbonate / dimethyl carbonate (EC / DMC, 1:1vol) is absorbed into each composite film bonded to the positive and negative electrodes at 20 wt% of each composite film. The positive electrode unit is then bonded to the negative electrode unit to complete an integrated all-solid secondary battery. The polymer and solvent of the composite slurry phase used here can be the same or different, but for the conductive ceramic material, it is necessary to use a material suitable for the positive electrode in the positive electrode and a different material suitable for the negative electrode in the negative electrode. The total thickness of the two composite films between the electrodes is 80 μm.
[0085] Figure 5 is in accordance with Figure 2 The charge and discharge curves of the integrated all-solid secondary battery made by the method. 0.6 Co 0.2 Mn 0.2 O2 is used as the positive electrode and graphite is used as the negative electrode, and the discharge capacity of more than 130 mAh / g is continuously maintained.
[0086] Figure 6 is in accordance with Figure 3 The charge and discharge curves of the integrated all-solid secondary battery made by the method. 0.6 Co 0.2 Mn 0.2 O2 is used as the positive electrode and graphite is used as the negative electrode, and the discharge capacity of more than 140 mAh / g is continuously maintained.
[0087] Figure 7 is in accordance with Figure 4 The charge and discharge curves of the integrated all-solid secondary battery made by the method. 0.6 Co 0.2 Mn 0.2 O2 is used as the positive electrode and graphite is used as the negative electrode, and the discharge capacity of more than 140 mAh / g is continuously maintained.
[0088] Figure 8 It is in accordance with Figure 2 An integrated all-solid secondary battery made by the method and a secondary battery made by separately making a positive electrode, a negative electrode and a solid-phase electrolyte according to an existing method and then laminating them (the substances and contents used, the thickness of the solid-phase electrolyte and the Figure 2 The results of measuring the resistance of a battery (cell) made under the same conditions as in the previous example. Figure 8 As shown, the integrated all-solid secondary battery has lower resistance than existing secondary batteries.
[0089] The present invention can be implemented in many different ways and is not limited to the above-described embodiments.
Claims
1. A method for manufacturing an integrated all-solid secondary battery, comprising applying a mixed slurry comprising a conductive ceramic material, a polymer and a solvent to either side of an electrode by printing, doctor blade coating, spin coating or spray coating, removing the solvent by drying, and then immersing, dripping or pouring a liquid electrolyte formed by dissolving a lithium salt or a sodium salt in a non-aqueous organic solvent so as to absorb only the composite film comprising a conductive ceramic material and a polymer formed by removing the solvent, so as to form an integrated composite solid electrolyte on the electrode, and then covering the opposite electrode and pressing, wherein, When the sum of the conductive ceramic material and the polymer is taken as 100 wt %, the amount of the conductive ceramic material in the mixed slurry is 60 wt % to 99 wt %, and the amount of the polymer is 1 wt % to 40 wt %. The amount of the liquid electrolyte absorbed into the composite film is 1 to 20 parts by weight based on 100 parts by weight of the composite film including the conductive ceramic material and the polymer. The conductive ceramic material is lithium oxide, lithium phosphate, sodium super ion conductor or sodium oxide.
2. A method for manufacturing an integrated all-solid secondary battery, comprising applying a first mixed slurry comprising a conductive ceramic material, a polymer and a solvent to either side of an electrode by printing, scraping, spin coating or spraying, removing the solvent by drying, and then applying a second mixed slurry comprising a conductive ceramic material, a polymer and a solvent to a first composite film comprising a conductive ceramic material and a polymer formed by removing the solvent, removing the solvent by drying, thereby forming a multilayer composite film in which the second composite film is laminated on the first composite film, and by dipping, dripping or pouring, a liquid electrolyte formed by dissolving a lithium salt or a sodium salt in a non-aqueous organic solvent is absorbed only into the multilayer composite film to form an integrated composite solid electrolyte on the electrode, and then covering the opposite electrode and pressing, wherein, The second mixed slurry is different from the first mixed slurry, wherein: When the sum of the conductive ceramic material and the polymer is calculated as 100 wt %, the amount of the conductive ceramic material in the first mixed slurry is 60 wt % to 99 wt %, and the amount of the polymer is 1 wt % to 40 wt %. When the sum of the conductive ceramic material and the polymer is calculated as 100 wt %, the amount of the conductive ceramic material in the second mixed slurry is 60 wt % to 99 wt %, and the amount of the polymer is 1 wt % to 40 wt %. The amount of the liquid electrolyte absorbed into the multilayer composite film is 1 to 20 parts by weight based on 100 parts by weight of the multilayer composite film including the conductive ceramic material and the polymer. The conductive ceramic material is lithium oxide, lithium phosphate, sodium super ion conductor or sodium oxide.
3. A method for manufacturing an integrated all-solid secondary battery, comprising applying a first mixed slurry including a conductive ceramic material, a polymer and a solvent to a positive electrode by printing, scraping, spin coating or spraying, removing the solvent by drying, and then immersing, dripping or pouring a liquid electrolyte formed by dissolving a lithium salt or a sodium salt in a non-aqueous organic solvent to absorb only a first composite film including a conductive ceramic material and a polymer formed by removing the solvent, thereby forming a positive electrode unit integrating the positive electrode and the first composite solid electrolyte, applying a second mixed slurry including a conductive ceramic material, a polymer and a solvent to a negative electrode by printing, scraping, spin coating or spraying, removing the solvent by drying, and then immersing, dripping or pouring a liquid electrolyte formed by dissolving a lithium salt or a sodium salt in a non-aqueous organic solvent to absorb only a second composite film including a conductive ceramic material and a polymer formed by removing the solvent, thereby forming a negative electrode unit integrating the negative electrode and the second composite solid electrolyte, and then laminating and pressing the positive electrode unit and the negative electrode unit, wherein, The second mixed slurry is different from the first mixed slurry, wherein the process of forming the positive electrode unit and the negative electrode unit is performed simultaneously or sequentially, wherein: When the sum of the conductive ceramic material and the polymer is calculated as 100 wt %, the amount of the conductive ceramic material in the first mixed slurry is 60 wt % to 99 wt %, and the amount of the polymer is 1 wt % to 40 wt %. When the sum of the conductive ceramic material and the polymer is calculated as 100 wt %, the amount of the conductive ceramic material in the second mixed slurry is 60 wt % to 99 wt %, and the amount of the polymer is 1 wt % to 40 wt %. The amount of the liquid electrolyte absorbed into the first composite film is 1 to 20 parts by weight based on 100 parts by weight of the first composite film including the conductive ceramic material and the polymer. The amount of the liquid electrolyte absorbed into the second composite film is 1 to 20 parts by weight based on 100 parts by weight of the second composite film including the conductive ceramic material and the polymer. The conductive ceramic material is lithium oxide, lithium phosphate, sodium super ion conductor or sodium oxide.
4. The method for manufacturing an integrated all-solid secondary battery according to claim 2, characterized in that: The multi-layer composite film further includes a composite film different from the first composite film and the second composite film.
5. The method for manufacturing an integrated all-solid secondary battery according to claim 3, characterized in that: Any one or both of the positive electrode unit and the negative electrode unit further includes a composite film different from the first composite film and the second composite film.
6. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The solvent used in the mixed slurry including the conductive ceramic material, polymer and solvent is: N-methyl-2-pyrrolidone or its derivatives, acetone or its derivatives, ethanol or its derivatives, methanol or its derivatives, dimethylacetamide or its derivatives, tetrahydrofuran or its derivatives, dimethylformamide or its derivatives, distilled water or a mixture thereof.
7. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The non-aqueous organic solvent is: carbonates, esters, ethers, ketones, alcohols, aprotic solvents or a combination thereof.
8. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The lithium salt is: LiClO4, LiPF6, CF3SO2NLiSO2CF3, Li[N(SO2F)2], Li[B(C2O4)2], LiAsF6, (fluorosulfonyl)(trifluoromethanesulfonyl)lithium imide or a combination thereof.
9. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The sodium salt is: NaClO4, NaPF4, NaPF6, NaAsF6, NaTFSI, Na[(C2F5)3PF3], Na[B(C2O4)2], Na[N(SO2F)2], NaBeti(NaN[SO2C2F5]2) or a combination thereof.
10. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The lithium oxide conductive ceramic material is: Li-Al2O3; Li-β-Al2O3; Li-TiO2; Li-BaTiO3; Li-SiO2; (La, Li)TiO3, wherein (La, Li) = La or Li; Li5La3Ta2O 12 ;Li6La2CaTa2O 12 ;Li4SiO4Li3BO 2.5 N 0.5 ;Li9SiAlO8;Li6La2ANb2O 12 , where A=Ca or Sr; Li2Nd3TeSbO 12 ;Li7La3Zr2O 12 ;Li5La3Ta2O 12 ; Al2O3; or Li9SiAlO8.
11. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The lithium phosphate conductive ceramic material is: Li 1+x Al x Ge 2-x (PO4)3;Li 1+x Ti 2-X Al X (PO4)3;Li 1+x Ti 2- X Al x Si y (PO4) 3-y ;LiAl x Zr 2-X (PO4)3; or LiTi x Zr 2-x (PO4)3, Among them, 0 <x<2、0<y<3。 12. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The sodium oxide conductive ceramic material is: Na3Zr2Si2PO 12 .
13. The method for manufacturing an integrated all-solid secondary battery according to any one of claims 1 to 5, characterized in that: The polymer is: polyvinylidene fluoride or its copolymer, poly(vinylidene fluoride-co-trifluoroethylene) or its copolymer, polyethylene glycol (PEO) or its copolymer, polyacrylonitrile or its copolymer, poly(methyl methacrylate) or its copolymer, polyvinyl chloride or its copolymer, polyvinyl pyrrolidone or its copolymer, polyimide or its copolymer, polyethylene or its copolymer, polyurethane or its copolymer, polypropylene or its copolymer, poly(propylene oxide) or its copolymer, poly(ethyleneimine) or its copolymer, poly(ethyl sulfide) or its copolymer, poly(vinyl acetate) or its copolymer, poly(ethylene succinate) or its copolymer, polyester or its copolymer, polyamine or its copolymer, polysulfide or its copolymer, siloxane or its copolymer, styrene butadiene rubber or its copolymer, carboxymethyl cellulose or its copolymer, or their derivatives, or their combinations.
14. An integrated all-solid secondary battery, characterized in that: Prepared according to the method according to any one of claims 1 to 5.
15. The integrated all-solid secondary battery according to claim 14, characterized in that: The thickness of the solid electrolyte between the positive electrode and the negative electrode is 20 μm to 150 μm.